Mirror clauses and mirror measures as instruments for protecting the European model of agriculture - Pastuszko, Radosław (Przegląd Prawa Rolnego, 2026)
This study aims to characterise mirror clauses and mirror measures as instruments for protecting the European model of agriculture. The liberalisation of agri-food trade has coincided with the tightening of environmental, sanitary, and animal welfare standards within the EU. At the same time, however, it has revealed the problem of double standards and regulatory asymmetry. The article advances the thesis that mirror instruments constitute a necessary, but not sufficient, means of safeguarding the competitiveness of European agriculture. Two main categories of mirror instruments are identified: treaty obligations and unilateral EU acts with extraterritorial effect. Tariff conditionality mechanisms may perform a similar function. The analysis encompasses the legal foundations of World Trade Organization (WTO) law as well as European Union law and selected sectoral regulations.